Embryonic development of the eggs of portunus pelagicus and charybdis feriatus crabs. - Pepino, Ma. Marivic C. (2011.)
A study was carried out to monitor and describe the embryonic developement of two commercially important swimming crbs, Portunus pelagicus and Charybdis feriatus. The stages of embryonic development of P. pelagicus and C. feriatus were described based on the distinct morphological features observable in live eggs. Eight stages of embryonic development were described and illustrated for the two portunid crabs. These include blastula ( stage I) whihc is hollow mass of cells produced by continuous cleavage and is the initial stage onserved; gastrula (stage 2) which was characterized by morphogenetic movements particularly involution; bud formation (stage 3) where cell proliferation and differentiation took place; nauplair (stage 4) in which major differentiation and growth were eveident; eye formation (stage 5) where ocular buds were eventually differentiated into a pigmened core (retina) with a white area (cornea); thoracic abdominal (stage 6) where in outline of cephalothorax and abdominal segmentation are observed; heartbeat stage 7) where heart is initially observed to beat slow and turned rapid until hatching; and pre-hatching (stage 8) in which yolk is almost completely depleted and structures are well differentiated. The mbryonic developments of the two crab species were similar; growth was synchronous, appendages were formed during the same periods and the complexity of the abdominal ocular processes were chronologically comaprable. The two crab species underwent the same pattern of changes in external egg colour. The results of the ivnestigation provided basic information on the biology of Charybdis feriatus and Portunus pelagicus, which is relevant to fisheries management, hatchery technology development and aquaculture .
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Portunus Crabs; Charybdis Crabs